O ensino de ciências e as relações entre escola e espaços não formais: um estudo com crianças ribeirinhas - Leal, Gyane Karol Santana (2014)
This work entitled: "Science teaching and the relationship between school and non-formal spaces: a study of riverside children" aims to understand how riverside children from a rural school located in the city of Parintins–AM build knowledge on Sciences through their experiences in the spaces of their community. It seeks the recovery of the history of children in Brazil and in the Amazon reflecting on how this generation has been constructed since the colonial period to the present day, bringing contribution from Childhood Sociology as it allows a new understanding of children in the perspective of knowledge subjects allowing listening to their voices, excluding the adult centrism. From this new view directed to childhood, we believe that riverside children can build scientific knowledge through the use of Amazonian non-formal spaces through their experiences and how this knowledge can be used by the school. In a research with children, it is necessary to use methodologies that make children the participants throughout the research process. To do so, it was necessary to request permission to parents and later, the collaboration of children. The participants were thirteen children in the age group from 3 to 5 years old and the class teacher. The data was being built through the interaction with the children, participant observation with notes in field diary, interviews and drawing analyses. It is concluded that children build scientific knowledge through their experiences in everyday life, in the interaction with peers and direct contact with multiple spaces in their community.